Strengthening smart digital marketing for millennials and economic growth in Indonesia - Sugiharto, Bambang; Harkim, Harkim; Nirmadarningsih Hiya; Agus Marwan (Institute of Computer Science (IOCS), 2024)
The existence of the millennial generation in Indonesia is currently one of the largest market shares for economic activities in this country. This study will discuss digital marketing in the Indonesian millennial generation. Today's empirical reality shows several phenomena, namely 1). The increasing growth and competition of online-based retail businesses 2). The development of software and technological infrastructure in digital marketing is increasingly innovative. 3) The behaviour of millennials in digital marketing and consumption is very prominent, becoming an unstoppable reality. This study was conducted using the angle of observation of this phenomenal empirical reality. The study is also strengthened by looking at the literature and previous studies. The result of this reflection is a comprehensive picture of Smart Digital Content Marketing with the main actors being Indonesian millennials. This study is expected to benefit Indonesian online businesses to further improve their digital content marketing with a smart approach.